Multi-criteria performance evaluation of a glass panel system using full-scale experimental data - Ilter, E.; Celik, O. C.; Ünlü, Gülten Aslıhan (Informa UK Limited, 2020)
In order to better evaluate the lifetime performance of glass panel facade systems, this study firstly proposes to conduct a full-scale wind resistance, air/water infiltration, and seismic resistan...
Keywords: Glass panel; Facade testing; Multi-criteria evaluation; Unitized facade; Experimental performance evaluation; Facade fatigue process